2017
DOI: 10.21533/isjss.v2i2.84
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Stress on the Health of Workers in Manufacturing Industry

Abstract: The frequent occurrence of stress and job-related-stress in recent times on workers at workplaces has become a trend of worry to: employers, management, employees, organizations, and society as a whole. Stress has a tremendous effect on job satisfaction, production, and workers' motivation. In this regard, the study methodology of this literature review focused on secondary sources of data. In-depth secondary sources of data was gathered to review trends of both past and current literatures and to elicit concl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…12,13 Increased stress levels are related to decreased job performance, higher medical costs, and impaired QoL. 14,15 A number of studies have reported significant association between psychological stressors and poor physical and mental health. 16,17 Furthermore, stressful life events are inversely related to QoL and well-being.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Increased stress levels are related to decreased job performance, higher medical costs, and impaired QoL. 14,15 A number of studies have reported significant association between psychological stressors and poor physical and mental health. 16,17 Furthermore, stressful life events are inversely related to QoL and well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Karamchandani et al (2020) reached the conclusion that occupational stress considerably and negatively impacted employee attitudes toward management. Multiple factors, according to Aidoo (2017), contribute to job stress and stress-related disorders. Among these elements are the environment, occupational demand (task), organizational structure, and work-life balance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Stress imposes a significant burden on the public. Increased stress levels are related to decreased job performance, higher medical costs, and poor relationships including family breakdowns leaving children unattended [ 12 ]. It also disrupts the whole life, health, and enjoyment of everyday activities [ 1 ].…”
Section: Introductionmentioning
confidence: 99%